Impact of Online Learning of Economics in Lebanon on Acquiring Essential Skills in Light of the COVID-19 Pandemic - El-Mousawi, Hasan; Zaraket, Mohamad; Bou-Assi, Claude (International Journal of Emerging Trends in Social Sciences, 2022)
The sudden and recent outbreak of the Covid-19 had its impact on the way of life around the entire world; it challenged the education systems around the globe and forced schools and universities to switch to online education overnight. Several schools and universities that were formerly hesitant to change their pedagogical approach had to switch completely to online education. The current paper explores the impact of online learning of Economics on acquiring essential skills in light of the Coronavirus outbreak from the economics teachers’ perspective. The researchers utilized a descriptive-analytical approach and constructed a quintet Likert style questionnaire which was electronically sent to a sample of Economics teachers working at Lebanese schools. The sample is made up of 153 teachers all of whom responded, and their responses were valid for analysis. The study rendered some noteworthy findings, mainly that through online learning of Economics, learners are not acquiring all of the 21st-Century skills. Based on the results, the researchers had some recommendations.